Human Resource Management in Education - Idris, Ahamd; Asep Marfu; Arif Fakih Firdaus; Siti Patimah; Rifyal Ahmad Lugowi (Mudir : Jurnal Manajemen Pendidikan, 2026)
This research aims to analyze the crucial role and implementation of Human Resource Management (HRM) in enhancing the effectiveness and quality of the education system. HRM in the educational context focuses on managing teaching and non-teaching personnel (teachers, lecturers, administrative staff) as the primary strategic asset of the institution. The methodology employed is a literature review (or case study/qualitative study, depending on the research focus) that explores current HRM practices across various educational levels. The findings indicate that effective HRM implementation covers several core functions, including: HR planning (forecasting needs for teachers and staff), recruitment and selection (ensuring relevant competencies and qualifications), career development and training (continuous professionalism and pedagogical improvement), performance appraisal (evaluation based on performance and its impact on student learning), and compensation and maintenance (fair incentives and a conducive work environment). This study concludes that an integrated and development-oriented HRM will directly contribute to improving the quality of learning, institutional productivity, and personnel job satisfaction. Key recommendations include the need to adopt an adaptive HRM framework, focus on talent management for high-performing teachers, and continuous investment in digital and pedagogical competency development. The application of strong HRM principles is essential for addressing the challenges of education in the modern era.